2006
DOI: 10.1063/1.2173033
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel based analysis of the thermoluminescence of CaSO4:RE (RE=Tm, Dy, Tb, and Sm)

Abstract: Vacuum ultraviolet spectroscopic properties of rare earth ( RE = Ce , Tb , Eu , Tm , Sm ) -doped hexagonal K Ca Gd ( P O 4 ) 2 phosphateThe thermoluminescence activation energy and frequency factor of the main glow of Ca S O 4 : Tm phosphor determined by heating rate method including very slow rates of heating Multitrapping levels feature of thermoluminescent ͑TL͒ phosphors of CaSO 4 :RE ͑RE= Dy, Tb, and Sm͒ were analyzed using a variable heating rate method ͑including extremely slow heating rates of 0.001°C s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Thus, the introduction of trivalent rare earth ions as luminescent center to matrices is considered as an excellent method for preparing superior luminescent material [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the introduction of trivalent rare earth ions as luminescent center to matrices is considered as an excellent method for preparing superior luminescent material [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…These sulphates are widely used for both individual and environmental radiation monitoring [1][2][3]. Their popularity has led to an extensive series of studies aimed at elucidating their behavior, attempting to assess the underlying mechanisms, and efforts to predict, or empirically develop new variants of these phosphors [4][5][6][7][8][9][10]. One particularly interesting result was reported by Dr Prokic who found that the addition of a lithium co-dopant during preparation of the CaSO 4 :Dy (or Tm) results in a major increase of luminescence efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, rare-earth-doped CaSO 4 shows useful thermoluminescence for the potential application in photoluminescence crystal liquid displays, optical storage materials, and cathodoluminescent materials. 18,19 Various methods have been used for the synthesis of CaSO 4 nanoparticles, [20][21][22][23] nanorods, 23 nanowires, 20,21,[23][24][25] and nanosheets, 21 such as water-in-oil microemulsion and reverse micelles, 20,23,26 a microwave-assisted method, 25 and a liquid-liquid separation method. 22 However, these methods have limitations in growth time, large quantity synthesis, and substrate synthesis.…”
mentioning
confidence: 99%